PERSONNEL SELECTION AS INFORMATION SECURITY CONTROLS - Kukharska , Nataliia; Lagun , Andrii (Ukrainian Scientific Journal of Information Security, 2022)
The article deals with current issues of human resource security in the context of ensuring the organization's information security. The focus is on the procedure of selecting applicants for vacant positions since mistakes made at this stage of personnel management can negatively affect the efficiency of the organization. The list of personal characteristics of employees that are dangerous from the point of view of information security is laid out. Based on the conducted research, recommendations were given regarding the use of non-traditional methods of checking and evaluating candidates for employment, namely: analysis of the applicant's profile in social networks; brainteaser interview; a method based on the use of physiognomy, studying the language of gestures and the body; graphological method; socionic typing method. The verification methods chosen by the organization must comply with the current legislation on confidentiality, protection of personal identification data, and employment. All regulations, moral and ethical standards, business requirements, perceived risks and the organization's information classification scheme must be taken into account, too.